2019
DOI: 10.1111/sode.12373
|View full text |Cite
|
Sign up to set email alerts
|

Joint and individual tool making in preschoolers: From social to cognitive processes

Abstract: Tool making has been proposed as a key force in driving the complexity of human material culture. The ontogeny of toolrelated behaviors hinges on social, representational, and creative factors. In this study, we test the associations between these factors in development across two different cultures. Results of Study 1 with 5-to-6-year-old Turkish children in dyadic or individual settings show that tool making is facilitated by social interaction, hierarchical representation, and creative abilities. Results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Developmental research has long demonstrated that collaborative learning bolsters children’s ability to solve novel tasks ( Azmitia, 1988 ; Perlmutter et al, 1989 ; Rendell et al, 2011 ) and their logical reasoning skills ( Tomasello et al, 1993 ; Kruger and Tomasello, 1996 ). Such socio-cognitive capabilities may also be central to children’s ability to make and innovate tools ( Gönül et al, 2019 ; Lew-Levy et al, 2021 ). Next, most experimental research on object play focuses on deferred functions related to tool use and tool making skill.…”
Section: Discussionmentioning
confidence: 99%
“…Developmental research has long demonstrated that collaborative learning bolsters children’s ability to solve novel tasks ( Azmitia, 1988 ; Perlmutter et al, 1989 ; Rendell et al, 2011 ) and their logical reasoning skills ( Tomasello et al, 1993 ; Kruger and Tomasello, 1996 ). Such socio-cognitive capabilities may also be central to children’s ability to make and innovate tools ( Gönül et al, 2019 ; Lew-Levy et al, 2021 ). Next, most experimental research on object play focuses on deferred functions related to tool use and tool making skill.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that when administering our tasks with a longer time window, more children will find solutions. To increase the ecological validity of such studies, future projects should provide longer testing times and more possible solutions, and arguably also administer tasks to pairs of participants instead to individuals only (see Gönül, Hohenberger, Corballis, & Henderson, 2019 ; Reindl & Wronski, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In psychology, innovation, and specifically, tool innovation, has been defined as the construction of ‘new tools, or using old tools in new ways, to solve new problems’ (Legare & Nielsen, 2015 , p. 689). Although innovative behaviours, including tool use and modification, have been described in other species (see Griffin & Guez, 2014 for review; Lefebvre et al, 2004 ; Overington et al, 2009 ; Reader et al, 2011 ), psychologists are often concerned with understanding the unique cognitive and developmental processes which underpin human innovation, including advanced analogical (Chan et al, 2011 ; Markman et al, 2011 ) or counterfactual reasoning (Tijus et al, 2009 ) to devise solutions, and inhibition (Gönül et al, 2018 ) or cognitive flexibility (Gönül et al, 2019 ; Pope et al, 2020 ) to apply them.…”
Section: Defining ‘Innovation’ Across Disciplinesmentioning
confidence: 99%
“…Although creative problem-solving metrics like divergent thinking (Gönül et al, 2019 ), floating object (Cheke et al, 2012 ; Hanus et al, 2011 ; Nielsen, 2013 ) and functional fixedness (Defeyter & German, 2003 ) tasks have been conducted alongside or as proxies for innovation metrics (Carr et al, 2016 ; but see Beck et al, 2016 ), here we focus on direct measures of tool innovation. For children, the most prevalent tool innovation metric is the hook task, a paradigm originally devised for corvids (Bird & Emery, 2009 ; Weir et al, 2002 ) and later modified for humans (Beck et al, 2011 ; Cutting et al, 2011 ).…”
Section: Experimental Research On Children As Innovatorsmentioning
confidence: 99%
See 1 more Smart Citation